2013
DOI: 10.1093/gbe/evt079
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Eukaryotic Chromosome: The Role of Noncanonical DNA Structures in Telomere Evolution

Abstract: The transition of an ancestral circular genome to multiple linear chromosomes was crucial for eukaryogenesis because it allowed rapid adaptive evolution through aneuploidy. Here, we propose that the ends of nascent linear chromosomes should have had a dual function in chromosome end protection (capping) and chromosome segregation to give rise to the “proto-telomeres.” Later on, proper centromeres evolved at subtelomeric regions. We also propose that both noncanonical structures based on guanine–guanine interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 95 publications
3
46
0
Order By: Relevance
“…1 A). The key points of CFTH described above have good support in the literature [Villasante et al, 2007a;Garavís et al, 2013]. However, the requirement for any scientific hypothesis is that it is testable.…”
Section: How Did the Centromere Evolve?mentioning
confidence: 86%
See 1 more Smart Citation
“…1 A). The key points of CFTH described above have good support in the literature [Villasante et al, 2007a;Garavís et al, 2013]. However, the requirement for any scientific hypothesis is that it is testable.…”
Section: How Did the Centromere Evolve?mentioning
confidence: 86%
“…The first assumption of CFTH is that eukaryogenesis was prompted by the adaptation of the bacterial symbiont and the archaeal host to their new conditions. As part of the adaptation process, the symbiont's class II introns, a class of retrotransposons, invaded the host's circular genome and caused its fragmentation into linear DNA molecules [Garavís et al, 2013]. The genome fragmentation resulted in free DNA ends which became opportunistic targets for mobile genetic elements from the host's genome, such as non-LTR retrotransposons, eventually leading to stabilization of free DNA ends and formation of proto-telomeres resulting in the formation of the first proto-eukaryotic linear chromosomes [Garavís et al, 2013].…”
Section: Telomere Length Regulation In the Light Of Cfthmentioning
confidence: 99%
“…However, at that time this motif was detected only on chromosomes of certain aculeate Hymenoptera, i.e., the honeybee, Apis mellifera Linnaeus, 1758, from the family Apidae as well as about 20 ant species (Formicidae), using either FISH or SBH (Lorite, Carrillo, & Palomeque, 2002;Meyne & Imai, 1995; see also Korandová et al, 2014;Okazaki et al, 1993;Pereira, dos Reis, Cardoso, & Cristiano, 2018;Wurm et al, 2011). Interestingly, the telomeres of A. mellifera appeared to be a mosaic of short TTAGG repeats interspersed with TCAGGCTGGG, TCAGGCTGGGTTGGG, and TCAGGCTGGGTGAGGATGGG higher order repeat arrays (Garavís et al, 2013). Furthermore, the first fully sequenced parasitoid genome of Nasonia vitripennis (Walker, 1836) (Chalcidoidea, Pteromalidae), together with genomes of two other members of the same genus, was found to lack the TTAGG telomeric repeat, although the seemingly intact telomerase gene was detected in has been demonstrated by Gokhman and Kuznetsova (2018).…”
Section: Coleoptera (Beetles)mentioning
confidence: 99%
“…The latter mechanism therefore usually activates when normal functioning of the telomerase becomes problematic (Osanai, Kojima, Futahashi, Yaguchi, & Fujiwara, ). Nevertheless, both telomeric repeats and telomerase (as well as the telomerase‐coding gene) lack in all studied members of the order Diptera (Garavís, González, & Villasante, ; Rosén, Kamnert, & Edström, ) suggesting that this mechanism is fully replaced by ALT.…”
Section: Introductionmentioning
confidence: 99%
“…However, this alternative can be ruled out in our target taxa, since no ITS co-localized with the NORs in any of species examined here. Finally, telomeres appear to be the evolutionary precursors of eukaryote centromeres [Villasante et al, 2007;Mendez-Lago et al, 2009; 300 Garavis et al, 2013], and telomeric DNA may give rise to neocentromeres [Villa sante et al, 2007;Ishii et al, 2008] as reported in plants, invertebrates, and mammals [Fukagawa and Earnshaw, 2014;Steiner and Henikoff, 2015]. But whether some of the observed turtle ITS represent evolutionary neocentromeres remains to be tested.…”
Section: Turtle Telomere Evolutionmentioning
confidence: 99%